Bahasa Inggris - Ninasafitri; Ayub Pratama Aris; Yayu Indriati Arifin; Zeffitni (Postgraduate, University of Mataram, 2023)
Geoconservation is an important effort in preserving geological diversity. Geoparks act as a link to encourage geoconservation. This research aims to evaluate the geology, geosite potential and groundwater availability in Olele Village, Gorontalo. This research aims to determine geological conditions, geosite potential, groundwater availability and groundwater conservation measures. The methods of literature survey, field survey, field data collection and ArcGis 10.8 data analysis were used. Stratigraphy shows the sequence of Reef Limestone (Ql), Pinogu Volcanic Rock (TQpv), Bone Diorite (Tmb), and Bilungala Volcanic Rock (Tmbv). Geomorphology includes reef terrace plains, alluvial plains, pyroclastic flow hills, and lava flows. Lithological contacts between reef limestone and pyroclastic breccia mark the Olele Geosite. Water quality is influenced by the level of rock passability and rainfall. Olele Village has good groundwater potential with a groundwater table depth of 1-8 meters. Groundwater conservation measures involve monitoring, public education, water use management, sustainable agriculture, wetland rehabilitation, development of alternative infrastructure, and mitigation of tourism impacts. Thus, this research emphasizes the need for sustainable strategies for the conservation of geological and groundwater resources in this area.